Oral health in home care within the scope of the family health strategy: A look at public policy - Filho, Sergio Henrique Cesar; Laporte, Kenia; Oliveira, Dandara Curitiba; Silva, Alan Patricio da (Seven Editora, 2023)
Introduction: With the action initiated from the institutionalization of the Declaration of Alma Ata (1978), Primary Health Care (PHC) seeks to achieve the objective of offering universal primary care necessary for the community. In this service, there is the Family Health Strategy (FHS), in which the monitoring of the health territory is carried out, with actions and monitoring of the population by a team. Among the professionals who should compose the FHS team, there are the dentist and the auxiliary or technician in oral health, which, in addition to allowing the expansion of the population's access to services, promote intervention in the determinants of health and the improvement of existing oral health-disease problems. It is noteworthy that the absence or ineffectiveness of oral health care can affect the general well-being of users, resulting in infections in the oral cavity, which, in turn, can result in or aggravate other health problems.  Therefore, there is a need to look at those patients who, due to their health conditions, do not meet the conditions to use the dental service in the Basic Health Unit itself, thus requiring home oral health care. Thus, the present work proposes a discussion about the importance of public policies aimed at home care in oral health, more particularly, to describe and analyze the lack of actions of this nature aimed at this population. Objective: To discuss the implementation of oral health in home care, within the scope of the Family Health Strategy. Methodology: This study is a reflective theoretical essay based on the theme of Primary Health Care, its theoretical foundation from the national and international scientific literature and the critical analysis of the authors. Thus, the reflection on the theme and its explanations will be the guiding axis on the subject. As there was no interaction of direct/applied research, the need to submit the study to ethical procedures was excluded. Conclusion: This research aims to gather subsidies to reevaluate the planning of oral health actions and services aimed at the public discussed here and the possible obstacles to the provision of this care, indispensable for the promotion of general health and well-being. DOI:https://doi.org/10.56238/innovhealthknow-005